Qualitative Systematic Review in Applied Linguistics: A Synthesis - Zhang, Jinpei (International Journal of Language and Literary Studies, 2023)
Qualitative Systematic Review (QSR) is the second-generation literature review that aims to synthesize primary qualitative studies. Its use is growing rather rapidly in medicine, nursing, education and other fields, but it remains underutilized in applied linguistics. In order to invite more qualitative systematic reviews in applied linguistics, this paper first provides the definition of QSR, outlines the key steps for its conduct, elaborates on the core procedure, i.e., synthesis methods, then illustrates with published examples of qualitative systematic reviews in applied linguistics, and finally explores the future directions.